2020
DOI: 10.1097/sih.0000000000000432
|View full text |Cite
|
Sign up to set email alerts
|

Inspiring Young Learners Toward a Career in Healthcare Using Simulation

Abstract: Summary Statement To inspire young learners toward a career in healthcare and provide them opportunities to learn lifesaving skills, a hospital-based simulation center collaborated with a local middle school to develop a 88-minute simulation-based educational activity. The activity consisted of eight 10-minute stations on lifesaving and basic medical skills. One hundred fifty students participated. Evaluation surveys showed students favored stations with extensive hands-on activities and valued the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…High school students are particularly enthusiastic to learn about future career options, whether that is to consolidate their current interests or gain knowledge of other roles in health care. 23 For those students who continue to pursue their interest in medical studies, the experience promoted the multidisciplinary nature of working as a health professional and provided students with an insight into the function of an effective team with a common goal. This style of learning can also prepare students for the learning experience at university, such as problem-based learning experiences common in medical and health professions training.…”
Section: Discussionmentioning
confidence: 99%
“…High school students are particularly enthusiastic to learn about future career options, whether that is to consolidate their current interests or gain knowledge of other roles in health care. 23 For those students who continue to pursue their interest in medical studies, the experience promoted the multidisciplinary nature of working as a health professional and provided students with an insight into the function of an effective team with a common goal. This style of learning can also prepare students for the learning experience at university, such as problem-based learning experiences common in medical and health professions training.…”
Section: Discussionmentioning
confidence: 99%
“…19 Several studies have demonstrated that effective feedback improves the performance of all learners in the OR. 10,2023…”
Section: Feedback and Postoperative Debriefingmentioning
confidence: 99%
“…19 Several studies have demonstrated that effective feedback improves the performance of all learners in the OR. 10,[20][21][22][23] Video review has emerged as a valuable strategy as part of comprehensive coaching to evaluate trainee technical skills and address potential variability observed in clinical outcomes such as surgical complications and postoperative recovery. This approach has proven beneficial for trainees as it fosters significant improvement in their surgical competence while also contributing to enhanced safety metrics in the clinical setting.…”
Section: Feedback and Postoperative Debriefingmentioning
confidence: 99%